Analisis Respon Mahasiswa Terhadap Pembelajaran Tatap Muka Setelah Pandemi Covid-19 - Nadia Eka Putri Indriani; Agung Sulaiman (PAKAR Pendidikan, 2023)
The outbreak of the Coronavirus Disease 2019 (Covid-19) pandemic that occurred in Indonesia resulted in all aspects of life being greatly disrupted, including the education sector. During the Covid-19 pandemic, various ways have been carried out by various schools for ongoing learning such as applying bold learning and alluring learning. Although sometimes the learning objectives to be achieved have not been achieved properly, but what is expected from the process is that students are expected to be able to receive learning, both bold learning and compelling learning, including the efforts made by schools to educate their students. This study aims to determine the response of students to face-to-face learning after the COVID-19 pandemic at Padang State University. The research method used is a descriptive research method using surveys with data collection techniques in the form of filling out questionnaires through google forms. The number of samples in this study was 60 people. Data collection using a survey method with a likert scale. Data analysis by calculating the percentage of data on each indicator, then interpreting the percentage score of the data and analyzed descriptively on each indicator. Research analysis shows that students' response to face-to-face learning is very effective and efficient to do and is in the category of quite good (41.5%). The results of this study are also expected to be a reference in the development of face-to-face learning in higher education and as study material for subsequent research related to face-to-face learning after the Covid-19 pandemic.